Pemberdayaan pada SD Negeri 009 Bintan Timur Kabupaten Bintan melalui Penguatan Literasi Berbasis Kemaritiman bagi Anak Pesisir Kelurahan Gunung Lengkuas - Baharudin Baharudin; Yodha Mahardika; Rizky Aprilia; Suci Nayla Nur Cahya; Rahmadatul Ania; Rahman Rahman; Windy Febri Dyana Sinaga; Cheline Shismitupa Sidabutar; Citra Viona; Nur Nayla Tri Ananda; et al. (Jurnal Pengabdian Masyarakat, 2026)
As a maritime nation, Indonesia needs to strengthen maritime literacy from an early age, especially for children living in coastal areas. However, initial observations at SD Negeri 009 Bintan Timur indicate that maritime literacy has not been a primary focus of learning, resulting in low student understanding and awareness of local maritime potential. This community service activity aims to strengthen maritime-based literacy for coastal children in Gunung Lengkuas Village through participatory and fun learning methods. The activity was conducted in January 2026 with 26 sixth-grade students using an Experiential Learning approach that combines interactive lectures, educational games, coloring activities, and questionnaire evaluations. Results showed an increase in students’ understanding of basic maritime concepts, marine resource potential, and the importance of environmental sustainability, as evidenced by the predominance of "I Know" responses for most of the evaluation items. However, there remains a knowledge gap regarding the potential for local fisheries cultivation. Overall, this program was effective in fostering awareness and love of the ocean among coastal children.